DIGITALISASI MANAJEMEN LABORATORIUM FARMASI PADA POLTEKKES KEMENKES JAMBI BERBASIS WEB - Marwah, S.; Puspitorini, Sukma; -, Pariyadi (LP2M Universitas Nurdin Hamzah, 2024)
Laboratory Management is a systematic process that involves collecting, storing, maintaining, processing, retrieving, and validating data required by the laboratory to make informed management decisions. The Department of Pharmacy at Politeknik Kesehatan Kementerian Kesehatan (Poltekkes Kemenkes) Jambi needs a management system that can handle a significant amount of data. The current laboratory management system is not digitalized, which has led to inadequate documentation of inventory data, borrowing and returning of lab equipment and tools, as well as other relevant information related to schedules and student final projects. Therefore, the objective of this research is to develop a web-based information system for laboratory management. The system will assist laboratory staff in managing data and information related to practicums and laboratory activities. Input data are inventory of laboratory tools and materials data, lab schedule data, and lab activity data. The system output will provide tool and material inventory data reports, as well as reports on the use and borrowing of tools and materials. This research has resulted in the development of a Laboratory Management Information System that assists laboratory managers in managing inventory and laboratory activity data.